Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Loyalitas Pelanggan Pada Rayana Outfit - Hartati, Ria Marlia; Mubarok, Dadan Abdul Aziz (IKRAITH-EKONOMIKA, 2025)
This study aims to analyze the influence of service quality and trust on customer loyalty at Rayana Outfit. The research method used a quantitative approach with a sample of 75 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results show that service quality and trust have a significant positive effect on customer loyalty. Trust has a more dominant influence than service quality. The study recommends that Rayana Outfit improve service quality and implement a more competitive customer trust strategy to increase customer loyalty.